2006
DOI: 10.1074/jbc.m510275200
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide-binding Oligomerization Domain-1 and Epidermal Growth Factor Receptor

Abstract: Host-pathogen interactions that allow Helicobacter pylori to survive and persist in the stomach of susceptible individuals remain unclear. Human ␤-defensins (hBDs), epithelial-derived antimicrobial peptides are critical components of host-defense at mucosal surfaces. The role of H. pylori-mediated NF-B and epidermal growth factor receptor (EGFR) activation on ␤-defensin expression was investigated. Transient transfection studies utilizing ␤-defensin promoter constructs were conducted in gastric cells with cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(42 citation statements)
references
References 69 publications
0
41
1
Order By: Relevance
“…In addition, transactivation of EGF receptor during human skin wound healing stimulates hBD-3 expression in skin keratinocytes (Sorensen et al, 2006). While signaling pathways that regulate expression of hBD-1 still remain unknown, hBD-2 is induced by pro-inflammatory mediators or bacterial products via activation of NF-κB transcription factors and STATs (Boughan et al, 2006; Chung and Dale, 2008). Kawsar et al (2010) have shown the expression of hBD-2 in microvasculature in the “keratin pearl” region of terminally differentiated OSCC.…”
Section: β-Defensins In Cancermentioning
confidence: 99%
“…In addition, transactivation of EGF receptor during human skin wound healing stimulates hBD-3 expression in skin keratinocytes (Sorensen et al, 2006). While signaling pathways that regulate expression of hBD-1 still remain unknown, hBD-2 is induced by pro-inflammatory mediators or bacterial products via activation of NF-κB transcription factors and STATs (Boughan et al, 2006; Chung and Dale, 2008). Kawsar et al (2010) have shown the expression of hBD-2 in microvasculature in the “keratin pearl” region of terminally differentiated OSCC.…”
Section: β-Defensins In Cancermentioning
confidence: 99%
“…NOD1 sensing of H. pylori peptidoglycan induces NF-κB activation and expression of type I IFN via IFN-Regulatory-Factor 7, MIP-2, and β-defensin (14,15,20,22) and H. pylori colonizes Nod1 −/− deficient mice more densely compared to wild-type mice (14,22). In humans, genetic variation in ATG16L1 , which encodes a key effector of NOD1-dependent autophagy and inflammation, alters susceptibility to H. pylori infection (25).…”
Section: Introductionmentioning
confidence: 99%
“…Although Nod2 recognizes the muramyl dipeptide (MDP) structure in bacterial peptidoglycan (PGN)-related molecules, Nod1 senses the essential iE-DAP dipeptide, which is uniquely found in PGN of all Gram-negative and certain Gram-positive bacteria (8 -12). Previous studies suggested the involvement of Nod1 in the recognition of numerous bacteria including Helicobacter pylori (13,14), Listeria monocytogenes (15, 16), Shigella flexneri (17), several Bacillus species (18), and Propionibacterium acnes (7). Although the iE-DAP structure is found in the insoluble fraction of intact PGN, intermediates of PGN synthesis and cleaved PGN products produced during bacterial growth and PGN recycling (11,19), the identity of the major Nod1 stimulatory molecule (s) remains unknown (18).…”
mentioning
confidence: 99%